Subcutaneously administered dexmedetomidine is efficiently absorbed and is associated with attenuated cardiovascular effects in healthy volunteers - P. Uusalo; D. Al-Ramahi; I. Tilli; R. A. Aantaa; M. Scheinin; T. I. Saari (Springer Verlag, 2022)
Purpose: Palliative care patients often need sedation to alleviate intractable anxiety, stress, and pain. Dexmedetomidine is used for sedation of intensive care patients, but there is no prior information on its subcutaneous (SC) administration, a route that would be favored in palliative care. We compared the pharmacokinetics and cardiovascular, sympatholytic, and sedative effects of SC and intravenously (IV) administered dexmedetomidine in healthy volunteers.
Methods: An open two-period, cross-over design with balanced randomization was used. Ten male subjects were randomized to receive 1 μg/kg dexmedetomidine both IV and SC. Concentrations of dexmedetomidine and catecholamines in plasma were measured. Pharmacokinetic variables were calculated with non-compartmental methods. In addition, cardiovascular and sedative drug effects were monitored.
Results: Eight subjects completed both treatment periods. Peak concentrations of dexmedetomidine were observed 15 min after SC administration (median; range 15–240). The mean bioavailability of SC dexmedetomidine was 81% (AUC0-∞ ratio × 100%, range 49–97%). The mean (SD) peak concentration of dexmedetomidine in plasma was 0.3 (0.1) ng/ml, and plasma concentrations associated with sedative effects (i.e., > 0.2 ng/ml) were maintained for 4 h after SC dosing. Plasma noradrenaline concentrations were significantly lower (P < 0.001) within 3 h after IV than after SC administration. Subjective scores for vigilance and performance were significantly lower 0–60 min after IV than SC dosing (P < 0.001 for both). The onset of the cardiovascular, sympatholytic, and sedative effects of dexmedetomidine was clearly less abrupt after SC than IV administration.
Conclusions: Dexmedetomidine is relatively rapidly and efficiently absorbed after SC administration. Subcutaneous dexmedetomidine may be a feasible alternative in palliative sedation, and causes attenuated cardiovascular effects compared to IV administration.